Subjective poverty threshold in the Philippines - Bautista, Carlos C. (The Philippine Review of Economics, 2010)
Subjective poverty thresholds in the Philippines are derived from a 2003 household perception survey data set. The thresholds are computed using data on the minimum income question and actual income from the survey of 1,200 households.